2022
DOI: 10.1186/s41118-021-00149-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing mortality registration in Kerala: the MARANAM study

Abstract: Complete or improving civil registration systems in sub-national areas in low- and middle-income countries provide several opportunities to better understand population health and its determinants. In this article, we provide an assessment of vital statistics in Kerala, India. Kerala is home to more than 33 million people and is a comparatively low-mortality context. We use individual-level vital registration data on more than 2.8 million deaths between 2006 and 2017 from the Kerala MARANAM (Mortality and Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In the sixth paper in this Genus thematic series, Gupta and Mani ( 2022 ) construct annual life-tables from death registration and sample registration data by sex for the southern state of Kerala from 2006–2017. Their analysis shows that, for Kerala, mortality data from the civil registration system and sample registration system are consistent and the civil registration provides smoother rates, given its more comprehensive approach.…”
Section: Applications Of Demographic and Analytical Methods To The St...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the sixth paper in this Genus thematic series, Gupta and Mani ( 2022 ) construct annual life-tables from death registration and sample registration data by sex for the southern state of Kerala from 2006–2017. Their analysis shows that, for Kerala, mortality data from the civil registration system and sample registration system are consistent and the civil registration provides smoother rates, given its more comprehensive approach.…”
Section: Applications Of Demographic and Analytical Methods To The St...mentioning
confidence: 99%
“…Gupta and Mani ( 2022 ) make the important point that sustained improvements in the civil registration system in India are now making possible the production of high-quality mortality statistics from the official death registration system in some states of India. This point, also made by Rao and Gupta ( 2020 ), has at least three important policy implications.…”
Section: Applications Of Demographic and Analytical Methods To The St...mentioning
confidence: 99%
“…The median age of the reported deaths falls well below the most recent average life expectancy at birth of 78 years for women and 71 years for men. [ 32 ] The lack of a longevity advantage in women in COVID-19 deaths needs further exploration. Thus, exploring patterns discernible from available surveillance data remains useful.…”
Section: Discussionmentioning
confidence: 99%
“…We use these data instead of India's official population projections because the official projections do not provide state- and age-specific estimates of population for all the years we consider in our analysis. Previous work has shown that using the official estimates or those by the DHS makes little difference to demographic estimates ( Gupta & Mani, 2022 ).…”
Section: Methodsmentioning
confidence: 99%